Comparison of Two-Level and Three-Level Graded Collision Warning Systems Under Distracted Driving Conditions - Khatereh Shariatmadari; Siby Samuel; Shi Cao; Amandeep Singh (IEEE Access)
Advancements in vehicle technology such as collision warning systems are essential for improving driver alertness and decision-making to enhance road safety. This study evaluates the effectiveness of 2-level and 3-level graded collision warning systems on driver performance under various driving conditions. Forty participants participated in a controlled driving simulator study using a within-between-participant design to examine the impact of these warning systems on response time, collision frequency, physiological responses, and visual attention dynamics. The 3-level system providing graduated alerts through visual, haptic, and auditory cues, showed a significant reduction in response times and collision frequencies compared to the 2-level system. This improvement likely results from the multi-sensory approach that supports cognitive load theory and facilitates hazard detection. Although physiological measures such as Electrodermal Activity and Heart Rate did not show significant differences between the systems, the 3-level system produced more consistent responses suggesting a stable emotional state and reduced stress. Eye-tracking data indicated that the 3-level system improved sustained visual attention and reduced distraction. Subjective evaluations favored auditory warnings emphasizing the importance of user-friendly and intuitive systems. The findings demonstrate the potential of multi-level warning systems to enhance driver safety and performance in high-risk scenarios and suggest the need for customizable systems to accommodate individual differences in cognitive load management. These insights can inform developing advanced collision warning systems that mitigate risks associated with distracted driving and promote a safer driving environment.